Leakage current analysis of silicone rubber for high voltage insulation application - Nazir Ali, Nornazurah (2025)
The study of Silicone Rubber (SiR) polymeric outdoor insulating materials primarily focuses on enhancing their performance against ageing, allowing these materials to achieve a longer lifespan. To develop an optimised outdoor insulating material, both the material composition and processing parameters are investigated using the Design of Experiment (DOE) approach via Design Expert Software of two-level full factorial analysis. This study consists of two stages: the first to identify the best SiR mix based on selected parameters, and the second to test it under different operating conditions. The first stage evaluates four factors affecting SiR performance : A) Alumina Trihydrate (ATH) filler loading, B) Dicumyl peroxide (DCP) concentration, C) mixing speed, and D) mixing time, using leakage current (LC) as the performance indicator, based on Inclined Plane Tracking (IPT) test at 60 and 360 minutes as per BS EN IEC 60587:2022 standards. The data was collected using DAQ equipment and LabVIEW software, filtered in Python, and imported into Design Expert Software to analyse the influence of factors and their interrelations on LC values. Initially, at 60 minutes, the interrelation factor of AB had the most significant impact on LC, but by the end of the test at 360 minutes, factor A was deduced as the dominant factor. Next, the optimised SiR blend with the lowest LC (0.690588 mA) at 360 minutes was found, which is Sample 5, consisting of 50 pphr of ATH, 0.5 pphr of DCP, a mixing speed of 70 rpm, and a mixing time of 10 minutes, with desirability of 1 and a good Capability Process Index (Cpk) of 2.14, ensuring the quality and consistency of the samples' reproducibility in manufacturing. To support these findings, additional analyses were conducted, including weight loss evaluation, mechanical testing of tensile strength, morphological examination via Scanning Electron Microscopy (SEM), and chemical characterization through Fourier Transform Infrared Spectroscopy (FTIR).The optimised sample showed the lowest LC, high tensile strength, and smaller FTIR peak changes after the IPT test compared to other samples. The surface image analysis using SEM revealed a distinct impact of ageing, which was particularly severe for samples with the lowest ATH and highest LC values. The optimised blend was then replicated for further analysis in the second stage, and the focus now shifts to identifying the endurance and performance of the optimised sample under several critical factors during SiR degradation, again under the IPT test. This time, the factors were set to A) voltage, B) contaminant flow rate, and C) contaminant concentration. The interrelations between the factors and their influence on SiR’s LC values and the maximum withstandable LC of optimised SiR sample were discovered. In both periods of 60 and 360 minutes, factor C emerged as the most significant, followed by B and A. The maximum LC values that the optimised samples could withstand under various circumstances were also determined, and it was found that even when all factors were set to their maximum, the LC remained below 60 mA, in line with the standard requirements. In conclusion, the statistical analysis demonstrates that it is possible to optimise SiR to achieve excellent electrical, physical, mechanical, and chemical properties by adjusting material composition and processing parameters. The findings also revealed the interrelation between various factors and their impact on SiR performance, allowing for future adjustments to achieve a desired SiR with a specific LC output.